2010
DOI: 10.1021/cg100165t
|View full text |Cite
|
Sign up to set email alerts
|

Solid State Forms of Theophylline: Presenting a New Anhydrous Polymorph

Abstract: A previously unreported anhydrous polymorph (Form IV) of theophylline has been crystallized and characterized. Solubility determination, crystallization, and equilibration experiments indicated that Form IV is the most thermodynamically stable anhydrous polymorph. The hydration behavior of theophylline was investigated by three different methods: solubility, crystallization, and slurry experiments. The value of water activity at which the monohydrate form of theophylline becomes the most thermodynamically stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
71
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 22 publications
8
71
0
Order By: Relevance
“…[37][38][39][40][41][42] Recently, a new anhydrous form IV has been reported. 43,44 However, reproduction of this form following the published procedure of slurry conversion in methanol failed in our hands. Another crystal form has been reported to be obtained by antisolvent precipitation using supercritical CO 2 and CHF 3 as antisolvent.…”
Section: Introductionmentioning
confidence: 95%
“…[37][38][39][40][41][42] Recently, a new anhydrous form IV has been reported. 43,44 However, reproduction of this form following the published procedure of slurry conversion in methanol failed in our hands. Another crystal form has been reported to be obtained by antisolvent precipitation using supercritical CO 2 and CHF 3 as antisolvent.…”
Section: Introductionmentioning
confidence: 95%
“…48 A new nonsolvated polymorphic form of theophylline has been crystallized and shown by a number of measurements to be the most thermodynamically stable anhydrous crystal form. 49 This form-IV exhibited the lowest solubility in methanol, with forms I and II being found to undergo solvent-mediated phase transformations into form-IV if the slurry was allowed to stand for a sufficient amount of time. The nonsolvated forms I, II, and IV were all stable in the solid state, but all three forms would convert to the monohydrate in aqueous suspensions.…”
Section: Structural Characterization and Properties Of Polymorphs Andmentioning
confidence: 97%
“…40,[41][42][43][44][45][46] Form II (orthorhombic, space group Pna2 1 ), is the most commonly encountered polymorph, and was long believed to be the thermodynamic form of theophylline under ambient conditions, though it has recently been shown that Form IV is in fact more stable. 47 The crystal structure of Form II was determined by…”
Section: Introductionmentioning
confidence: 99%